PENANGGULANGAN STUNTING MELALUI COLLABORATIVE GOVERNANCE DI KABUPATEN PEMALANG PROVINSI JAWA TENGAH - Ane Permatasari; Galih Prasongko (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2025)
The problem of stunting is currently a big problem both in the world and in Indonesia. Stunting occurs due to malnutrition in the first 1000 days of life which at this time is the golden period of human growth and development. The Indonesian government continues to assess and implement stunting prevention and control programs in Indonesia. This is also done by the Central Java Government in dealing with stunting by making a zoning map of areas focused on handling stunting. Pemalang Regency is included in the focus of preventing stunting prevention and reduction, considering that Pemalang Regency has a fairly high number of stunting cases, which is 22.94%. The purpose of this study is to analyze how the efforts made by the local government and the implementation of collaborative governance in the prevention and handling of stunting cases in Pemalang Regency. This research uses a qualitative type of research because the problem of this research is related to humans who fundamentally depend on observation. Data collection is sourced from primary data, interviews from government and private agencies in the implementation of collaborative governance, and secondary data on documents obtained from literature studies. The results show that the implementation of collaborative governance in the prevention and control of stunting in Pemalang Regency has been running well. In addition, the collaborative governance carried out has proven to have a significant impact on reducing the number of stunting rates from year to year in Pemalang Regency.